Multiple access based on three-stage modulation in multi-band OFDM-UWB system - BAO Zhi-hua; ZHANG Shi-bing; ZHANG Guo-an; QIN Jin-jing (Tongxin xuebao)
According to the characteristics of multi-band orthogonal frequency-division multiplexing ultra-wideband（OFDM-UWB） system,a multiple access based on three-stage modulation（TSM-MA） was proposed.It combined multi-carrier code division multiple access（MC-CDMA） with orthogonal frequency division multiple access（OFDMA） and frequency hopping multiple access（FHMA）,carried out the advantages of the three multiple access techniques.It reduced the multiple access interference and made full use of the available resource of the channel.The two-stage spread spectrum and two-stage frequency hopping were used to the TSM-MA for reducing the complexity of receiver.Simula-tion results showed that TSM-MA has obvious advantages in bit error rate（BER） performance over time frequency code multiple access（TF-MA） about 3 dB and lower complexity than that of TF-MA.